Symmetrical and Peripheral Gangrene Complicating a Third-Degree Atrioventricular Block: A New Presentation of a Known Disease - Aissaoui, Hanane (Cureus, 2020)
Symmetrical peripheral gangrene (SPG) is a rare, serious entity characterized by ischemic changes of the distal extremities with no vessel occlusion, leading to fatal complications. It is related to numerous causes, and the treatment is not yet consensual. We present the first case of SPG related to low cardiac output secondary to a third-degree atrioventricular block. Physicians should be aware of this entity, as early recognition and adequate management can help in reducing morbidity and mortality and prevent fatal complications.